2023
DOI: 10.1039/d2fo03957e
|View full text |Cite
|
Sign up to set email alerts
|

In vivo administration of gut bacterial consortia replicates urolithin metabotypes A and B in a non-urolithin-producing rat model

Abstract: Urolithins (Uros) production capacity and, consequently, at least partly, the health effects attributed to ellagitannins and ellagic acid consumption vary among individuals. The reason is that not all individuals have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Recently, Iglesias-Aguirre et al reported two co-cultures able to convert ellagic acids into urolithins reproducing urolithin metabotypes A and B using only two gut bacteria per co-culture and the administration of these bacterial consortia successfully replicated urolithin metabotypes in rat. , Hence, new probiotic combinations could be formulated to engineer the gut microbiota of individuals unable to produce bioactive urolithins (urolithins metabotype 0) into urolithins metabotype A or B. Similar studies should be conducted to identify a bacterial consortium able to convert (−)-epicatechin, or more generally flavan-3-ols, into 3,4-DHPVL.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Iglesias-Aguirre et al reported two co-cultures able to convert ellagic acids into urolithins reproducing urolithin metabotypes A and B using only two gut bacteria per co-culture and the administration of these bacterial consortia successfully replicated urolithin metabotypes in rat. , Hence, new probiotic combinations could be formulated to engineer the gut microbiota of individuals unable to produce bioactive urolithins (urolithins metabotype 0) into urolithins metabotype A or B. Similar studies should be conducted to identify a bacterial consortium able to convert (−)-epicatechin, or more generally flavan-3-ols, into 3,4-DHPVL.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the Enterocloster spp. have previously been shown to metabolize (dehydroxylate) uroC in vitro 36 and in vivo 37 under anaerobic conditions (Fig. 1A, full metabolic pathway in Extended Data Fig.…”
Section: A Subset Of Enterocloster Species Converts Urolithin C To Ur...mentioning
confidence: 95%
“…Recently, certain members of the Enterocloster spp. (Lachnospiraceae family) were reported to dehydroxylate uroC to uroA and isouroA to urolithin B (uroB) both in vitro and in vivo 38,39 .…”
Section: Mainmentioning
confidence: 99%
“…The potential to modulate UM is therefore worthy to explore. Recently, Iglesias-Aguirre et al 151 conducted an in vivo animal study to transfer urolithin-producing bacterial consortia with the aim to convert UM0 to UMA and UMB. Urolithin-producing bacterial strains, Gordonibacter and Ellagibacter , successfully colonised the rats’ gut and replicated the ability to produce urolithins.…”
Section: Introductionmentioning
confidence: 99%